2014
DOI: 10.1124/mol.114.095216
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidases as Novel Pharmacologic Targets against Influenza A Virus Infection

Abstract: Influenza A viruses represent a major global health care challenge, with imminent pandemics, emerging antiviral resistance, and long lag times for vaccine development, raising a pressing need for novel pharmacologic strategies that ideally target the pathology irrespective of the infecting strain. Reactive oxygen species (ROS) pervade all facets of cell biology with both detrimental and protective properties. Indeed, there is compelling evidence that activation of the NADPH oxidase 2 (NOX2) isoform of the NADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 199 publications
1
65
0
Order By: Relevance
“…Therefore, targeting the primary source of ROS production in inflammatory cells, that is the NOX2‐containing NADPH oxidase to attenuate ROS generation, may be an effective means for reducing the ROS‐induced viral burden and tissue damage. To support this notion, the specific deletion of the NOX2 gene was associated with improved lung function and a reduced amount of lung tissue damage . Our recent findings revealed that the primary subcellular site of ROS generation to influenza virus infection is the endosome .…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, targeting the primary source of ROS production in inflammatory cells, that is the NOX2‐containing NADPH oxidase to attenuate ROS generation, may be an effective means for reducing the ROS‐induced viral burden and tissue damage. To support this notion, the specific deletion of the NOX2 gene was associated with improved lung function and a reduced amount of lung tissue damage . Our recent findings revealed that the primary subcellular site of ROS generation to influenza virus infection is the endosome .…”
Section: Introductionmentioning
confidence: 87%
“…ROS, such as superoxide anion and hydrogen peroxide (H 2 O 2 ), are produced by mouse and human inflammatory cells in response to viral infection and enhance the pathology caused by viruses of low to high pathogenicity, including influenza A viruses 38 . The primary source of inflammatory cell ROS is the NOX2 oxidase enzyme 811 .…”
Section: Introductionmentioning
confidence: 99%
“…The primary source of inflammatory cell ROS is the NOX2 oxidase enzyme 811 . Although NOX2 oxidase plays a role in the killing of bacteria and fungi via phagosomal ROS production, NOX2 oxidase does not appear to eliminate viruses in a manner analogous to that for bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, low levels of ROS contribute to tumorigenesis either by stimulating DNA mutation or acting as second messengers involved in cancer cell survival [9,10], whereas high levels of ROS are linked to damage of cellular components, leading to cancer cell death [9]. In addition, it is experimentally confirmed that ROS are also involved in other diseases, including virus infection, neurodegenerative diseases, cardiovascular diseases, and immune disorder [11][12][13][14]. Unraveling the molecular mechanisms underlying redox regulation in cancer cells is therefore important and will assist in the development of novel therapeutic strategies.…”
mentioning
confidence: 96%